LEVANTAMENTO DE ESPÉCIES DANINHAS NA CULTURA DO PINUS EM AQUIDAUANA-MS NO PERÍODO SECO E CHUVOSO. - De Oliveira, Eli Domingos; Luzardo, Adriana; Gonçalves, Cristiane; Xavier, Thiago; Cavalcanti, Vittor (ANAIS DO ENIC, 2018)
-